Nickel‐Decorated Silver Nanowires for Polymer‐Based Magnetoelectric Composite. Issue 14 (12th May 2021) - Martin, Baptiste; Dantras, Eric; Lonjon, Antoine; Laffont, Lydia; Lacabanne, Colette
Abstract : Polymer‐based magnetoelectric composites are processed with an intrinsic piezoelectric poly(vinylidenefluoride‐ co ‐trifluoroethylene) (P(VDF‐TrFE)) matrix and high‐aspect‐ratio magnetic nickel–decorated silver nanowires. These core/ shell wires are obtained by the polyol reduction of Ni 2+ ions on high‐aspect‐ratio silver nanowires. Scanning electron microscopy and transmission electron microscopy analyses show a homogeneous and well‐crystallized nickel layer. Magnetic properties of the intrinsic particles and their composites are measured and show a strong enhancement of the coercive field compared to spherical Ni nanopowders. They also show the existence of strong magnetic anisotropy in the composites. The composites processed with a small amount of metallic particles (0.3 vol%) allow the maintaining of the P(VDF‐TrFE) crystalline phase and the ability of a macroscopic polarization. The latter is conducted under a 80 MV m −1 field, leading to a significant d 33 (3.2 pC N −1 ). Thus, the magnetoelectric properties are analyzed and an important coupling coefficient α ME equal to 1.8 V m −1 Oe −1 is measured. Abstract : Silver nanowires are decorated with nickel thanks to polyol reduction leading to ferromagnetic particles. Processing a 0.3 vol% P(VDF‐TrFE)/Ag@Ni nanowire (NW) composite allows the piezoelectric poling of the sample with a d 33 = 3.2 pC N −1 . Piezoelectricity and ferromagnetism coupling lead to a magnetoelectric coefficient in the composite. At room temperature, α ME is equal to 1.8 V m −1 Oe −1 .